Concentrations of isometamidium in the sera of cattle challenged with drug-resistant Trypanosoma congolense - Eisler, M.C.; Gault, E.A.; Moloo, S.K.; Holmes, P.H.; Peregrine, A.S. (Elsevier, 1997)
The relationship between serum concentrations of the prophylactic trypanocidal drug isometamidium chloride and protection against tsetse challenge with two populations of Trypanosoma congolense was investigated in Boran (Bos indicus) cattle, using an isometamidium-ELISA. Isometamidium chloride (Samorin) was administered to cattle at a dose rate of 1.0 mg/kg body weight by deep intramuscular injection. Thereafter, the animals were challenged at monthly intervals with either a drug-sensitive clone (T. congolense IL 1180) or a clone expressing a moderate level of resistance to isometamidium (T. congolense IL 3343). Untreated control cattle were used to confirm the infectivity of each challenge. Of ten drug-treated cattle that were challenged with T. congolense IL 3343, all were refractory to infection at the first challenge, 1 month after drug administration. However, all ten animals succumbed to infection at either the second (seven cattle) or third (three cattle) monthly challenges. By contrast, all five drug-treated cattle challenged with T. congolense IL 1180 resisted four monthly challenges. The mean isometamidium concentration at the time of the first, 1 month, challenge was 5.6 (+ or -) 2.8 ng/ml. At the time of the second monthly challenge the mean concentration was 2.0 (+ or -) 0.86 ng/ml; at this time, concentrations were not significantly different between those cattle refractory to challenge with T. congolense IL 3343 and those cattle that were not. Thus, differences in susceptibility to challenge at this time would appear to be due to differences in the drug sensitivity of the parasite challenge. Finally, the mean isometamidium concentration in uninfected cattle at the time of the fourth monthly challenge was 0.4 (+ or -) 0.18 ng/ml. These results indicate that when T. congolense infection occurs in cattle under isometamidium prophylaxis, the parasites may be considered at least moderately drug resistant if the concentration of isometamidium in serum is 2.0 ng/ml. At concentrations between 0.4 and 2.0 ng/ml a low level of drug resistance may be inferred. Below 0.4 ng/ml, however, no inference regarding drug resistance should be made.